THE ROLE OF E-COMMERCE EDUCATION IN SHAPING UZBEKISTAN’S DIGITAL ECONOMY - Sodikova Dilafruz (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This study introduces the E-Commerce Academy, an innovative, industry-driven learning platform designed to bridge the gap between academic knowledge and practical market needs in Uzbekistan. The academy provides flexible, interactive, and practice-oriented training in areas such as digital payments, logistics, marketing, and marketplace management, with programs tailored for beginners, intermediates, and advanced learners. It collaborates with universities, banks, and e-commerce platforms, offering certification systems that enhance professional credibility and entrepreneurial skills. A survey of 420 participants highlights strong demand for e-commerce education, particularly among young entrepreneurs, and reveals challenges such as limited knowledge, financial constraints, and digital literacy gaps. The results emphasize the socio-economic role of e-commerce education in fostering entrepreneurship, job creation, poverty reduction, and export growth. The E-Commerce Academy is positioned as a modern solution for Uzbekistan’s digital transformation, combining theoretical instruction with practical experience and industry partnerships.